Innovative mechanisms for implementing urban planning projects in a turbulent environment - Zahoretska, O.; Poltavets , Ihor; Tymofeev , Dmytro (Ways to Improve Construction Efficiency, 2023)
The article highlights a comprehensive study of innovative mechanisms for implementing urban planning projects in a turbulent environment caused by deep socio-economic upheavals, in particular, military operations in Ukraine, economic transformation, and destabilization of logistical and financial flows. The topic is extremely relevant, since effective project management in the field of urban planning requires adaptation to a constantly changing external environment, high flexibility of management decisions, the introduction of digital tools, and the integration of sustainable approaches to planning. The essence of innovation mechanisms as a multi-component system is revealed, including digital technologies (BIM, GIS, digital territorial management platforms), new forms of partnership (public-private partnership, collective investment, municipal agreements with international donors), flexible project and organizational models (agile, cascade-adaptive approach), as well as risk-oriented management tools. The article justifies the need to transition from a linear approach to management to iterative and adaptive models that allow for timely response to changes in the socio-political situation and resource conditions. The emphasis is placed on the fact that the implementation of urban development projects in such conditions requires complex interaction between state bodies, local governments, public organizations, donor structures and private business. The role of digital transformation in increasing transparency, manageability and predictability of the processes of implementing infrastructure initiatives is separately emphasized. The materials of the article can be used in the practice of municipal management, in the activities of development companies, in the implementation of programs for the reconstruction of affected territories, as well as in the preparation of strategic plans for community development. The presented analytical conclusions and the proposed model can serve as a theoretical and methodological basis for the development of effective management decisions in the field of urban development in conditions of high uncertainty and risks.